Skew angle estimation and alleviation based multi-layer perceptron in V-shaped read-head array BPMR systems - K. A. Fatika; Santi Koonkarnkhai; Piya Kovintavewat; Chanon Warisarn (AIP Advances, 2023)
The demand for a massive storage device has kept rising and it has led to the emergence of advanced technology with a vast storage capacity. Achieving this idea might bring some obstacles called two-dimensional interference as well as a skew angle (SA). Array-reader-based magnetic recording can be the potential to give a better performance in the system by reading multiple tracks simultaneously. This paper investigates a V-shaped read-head array (VRA) with three read sensors performance on five levels of skew angle consideration in three different zones of hard disk drive. VRA with three read sensors is being grouped; therefore, SA can be considered as the change in this group movement. To achieve a good system performance, we propose an SA estimation method for bit-patterned media recording systems by computing a specific target by three readback sequences before estimating the SA value and finally detecting the data. Both estimation and detection processes are carried out using a neural network method known as multilayer perceptron.
Keywords: Neural Networks and Applications; Iterative Learning Control Systems; Blind Source Separation Techniques